Contrasting Croatian deverbal nouns on –nje and Turkish deverbal nouns on -mA - Kerovec, Barbara (2013)
In Turkish as an agglutinative language many grammatical categories that are in Indo-European languages usually encoded lexically or syntactically are expressed morphologically. Among them is verbal category of voice. Passive, factitive, causative, reflexive and reciprocal are all in Turkish designated by different suffixes, while in Croatian as an Indo-European language they are expressed either lexically or syntactically. This paper aims to demonstrate how these typological differences in the two languages affect semantic load of deverbal nouns derived by the process of nominalization from conceptually close verbs in Turkish and Croatian (as the above cited verbs). The analysis focuses on contrasting primarily two types of deverbal nouns in the two languages: Croatian deverbal nouns ending with the suffix –nje and Turkish deverbal nouns ending with the suffix –mA. The reason why these two types of nouns are chosen for the analysis lies in the fact that they are both temporally neutral by contrast to Turkish deverbal nouns ending with the suffix –dIk or –(y)AcAk which do carry temporal meaning and which can not be semantically comparable to non of Croatian deverbal nouns but rather to Croatian subordinated clauses. The analysis of the two chosen types of deverbal nouns shows that Turkish nouns on –mA are semantically richer than Croatian deverbal nouns on –nje because they keep morphemes for voice originally included in the stems of the verbs from which they are derived. Croatian deverbal nouns on –nje do not keep any voice feature after nominalization which makes them semantically ambiguous from the point of view of the concepts of agent and patient of activity.